ACE Inhibition Modulates Myeloid Hematopoiesis after Acute Myocardial Infarction and Reduces Cardiac and Vascular Inflammation in Ischemic Heart Failure - Wolf-Stephan Rudi; Michael Molitor; Venkata Garlapati; Stefanie Finger; Johannes Wild; Thomas Münzel; Susanne H. Karbach; Philip Wenzel (MDPI AG, 2021)
Aims: Angiotensin-converting-enzyme inhibitors (ACE inhibitors) are a cornerstone of drug therapy after myocardial infarction (MI) and improve left ventricular function and survival. We aimed to elucidate the impact of early treatment with the ACE inhibitor ramipril on the hematopoietic response after MI, as well as on the chronic systemic and vascular inflammation. Methods and Results: In a mouse model of MI, induced by permanent ligation of the left anterior descending artery, immediate initiation of treatment with ramipril (10 mg/k/d via drinking water) reduced cardiac inflammation and the number of circulating inflammatory monocytes, whereas left ventricular function was not altered significantly, respectively. This effect was accompanied by enhanced retention of hematopoietic stem cells, Lin−Sca1−c-Kit+CD34+CD16/32+ granulocyte-macrophage progenitors (GMP) and Lin−Sca1−c-Kit+CD150−CD48− multipotent progenitors (MPP) in the bone marrow, with an upregulation of the niche factors Angiopoetin 1 and Kitl at 7 d post MI. Long-term ACE inhibition for 28 d limited vascular inflammation, particularly the infiltration of Ly6Chigh monocytes/macrophages, and reduced superoxide formation, resulting in improved endothelial function in mice with ischemic heart failure. Conclusion: ACE inhibition modulates the myeloid inflammatory response after MI due to the retention of myeloid precursor cells in their bone marrow reservoir. This results in a reduction in cardiac and vascular inflammation with improvement in survival after MI.